2022
DOI: 10.1155/2022/3242960
|View full text |Cite|
|
Sign up to set email alerts
|

Extraction of Intangible Cultural Heritage Visual Elements by Deep Learning and Its Application in Grassland Tourism of the Silk Road Culture

Abstract: Inner Mongolia is rich in grassland tourism resources, and the development of grassland tourism is of great significance to Inner Mongolia tourism and promotion of grassland protection. To better promote the grassland tourism of the Silk Road culture, the Conditional Global Area Network (CGAN) and Morphology Connected Component Chan-Vase (MCC-CV) algorithm are used to enhance and segment the traditional embroidery patterns in Inner Mongolia. Firstly, the generative adversarial network (GAN) is optimized, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…This will not only encourage the protection, inheritance and popularization of traditional culture but also promote the innovation of traditional crafts in the new era. Therefore, applying the AI technologies to embroidery has become a hot research topic (Fu, 2021; Wei, 2022; Bu and Jiang, 2022; Jimoh et al , 2021; Zheng et al , 2019; Zhou et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This will not only encourage the protection, inheritance and popularization of traditional culture but also promote the innovation of traditional crafts in the new era. Therefore, applying the AI technologies to embroidery has become a hot research topic (Fu, 2021; Wei, 2022; Bu and Jiang, 2022; Jimoh et al , 2021; Zheng et al , 2019; Zhou et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%